Law and Speed: Asylum Appeals and the Techniques and Consequences of Legal Quickening. (25th February 2020) - Hambly, Jessica; Gill, Nick
Abstract: This article examines how a politics of speed is manifest in a legal context via a detailed ethnography of the French National Court of Asylum (CNDA). It identifies the temporal, spatial, and organizational ordering techniques that characterize asylum appeals in France and discusses the consequences of these techniques for the way in which the appeal process is experienced by legal decision makers and subjects. It reveals adverse impacts of legal quickening on legal quality, in particular through identifying: 'cracks' in the performance of legal roles like lawyer and judge that begin to appear when law is executed rapidly and repetitively; dwindling opportunities to demonstrate and experience respect between parties; and the 'thinning‐out' of legal process, as heuristics rather than deliberation come to dominate legal reasoning. The article contributes to a burgeoning body of socio‐legal literature on law and time by establishing the negative impact of excessive legal quickening on role performance, respect, and legal quality.